2016
DOI: 10.1002/chem.201504649
|View full text |Cite
|
Sign up to set email alerts
|

Counterion‐Controlled Self‐Sorting in an Amphiphilic Calixarene Micellar System

Abstract: Molecular recognition of small molecules and ions by artificial receptors in microheterogeneous media such as micelles and vesicles can, in principle, provide better models of biological systems in comparison with bulk solutions. In this work we have investigated the complexation of an organic fluorescent probe with amphiphilic calixarene receptor below and above the critical micelle concentration (CMC). For concentrations below the CMC, the probe forms a host-guest complex with the calixarene behaving like a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…As aforementioned, one of the main challenges in using charged supramolecular receptors is the ubiquitous presence of their counterions, which not only alter the net charge of these hosts but also compete with the targeted guests for the complexation at the binding sites. [56,58,[62][63][64] For this reason, as a preliminary step, it is necessary to determine the extent of the coordination of bromide ion to P5A within the concentration range under investigation. Only then can a rigorous analysis of the complexation capacity of this macrocycle be conducted.…”
Section: Resultsmentioning
confidence: 99%
“…As aforementioned, one of the main challenges in using charged supramolecular receptors is the ubiquitous presence of their counterions, which not only alter the net charge of these hosts but also compete with the targeted guests for the complexation at the binding sites. [56,58,[62][63][64] For this reason, as a preliminary step, it is necessary to determine the extent of the coordination of bromide ion to P5A within the concentration range under investigation. Only then can a rigorous analysis of the complexation capacity of this macrocycle be conducted.…”
Section: Resultsmentioning
confidence: 99%
“…43 The affinity of 4 for cavitands 1−3 varies from 2.8 μM (2, pH 3.3) to 190 nM (3, pH 9.0), and >98% quenching of the fluorescence of 4 is observed upon binding. DSMI 5 has a size, shape, and charge profile that suggest it would be an excellent guest for 1−3 in water, and it is well-known to display enhanced fluorescence upon binding in hydrophobic environm e n t s , s u c h a s t h e c a v i t y o f h o s t m o l e c u l e s hexasulfonatocalix[6]arene 53,54 or cucurbit[7]uril. 55 Interestingly, DSMI 5 behaves quite differently to RhB guest 4: upon its binding to anionic cavitand 1, a strong enhancement in fluorescence of 5 is observed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Later, Fernandez-Abad and coworkers reported that DSMI (G7) could also decrease the CAC of 3 to 1.4 mM. 57 Moreover, it is also reported that the CAC of analogue 6 decreases in the presence of G45. 88 Aggregation of calixarenes bearing sulfonic groups at the lower rim could also be induced by cationic guests.…”
Section: Guest-induced Aggregation Of Hostmentioning
confidence: 96%